Combat sports in virtual reality for rehabilitation and disability adaptation: a mini-review - Yike Li; Chun Jiang; Hansen Li; Yuqin Su; Mengyao Li; Yang Cao; Yang Cao; Guodong Zhang; Guodong Zhang (Frontiers in Public Health)
This review examines the existing literature regarding the utilization of combat sports in virtual reality (VR) for disease rehabilitation and adaptive physical activity. A total of 18 studies were obtained from the Web of Science and Scopus databases. The results suggest that Boxing, the most studied combat sport in VR systems, has been primarily used to improve motor function and quality of life in patients with neurological conditions such as cerebral palsy, Parkinson’s disease, and stroke. Furthermore, VR combat sports have been shown to increase energy expenditure and physical activity intensity in individuals with disabilities, proving effective in maintaining overall physical health. Notably, VR boxing produces higher energy expenditure than other activities (e.g., tennis), with heart rate (HR) and oxygen consumption (VO2) during boxing sessions consistently exceeding those observed in tennis. Overall, research in this field remains limited and further explorations are warranted.